(untitled) (Revista Venezolana de Salud Pública, 2018)
A cross-sectional investigation was carried out with the objective of analyzing the clinical characteristics of the injuries caused by work-related accidents prevalent in workers of a Plastics Company. The population consisted of 105 records of medical records of workers who suffered accidents at work; 86 records formed the sample estimated by probabilistic sampling, the selection was made with the table of random numbers.